Multi-Pharmacology of Berberine in Atherosclerosis and Metabolic Diseases: Potential Contribution of Gut Microbiota - Yang, Shengjie; Li, Dan; Yu, Zongliang; Li, Yujuan; Wu, Min (Frontiers in Pharmacology, 2021)
Atherosclerosis (AS), especially atherosclerotic cardiovascular diseases (ASCVDs), and metabolic diseases (such as diabetes, obesity, dyslipidemia, and nonalcoholic fatty liver disease) are major public health issues worldwide that seriously threaten human health. Exploring effective natural product-based drugs is a promising strategy for the treatment of AS and metabolic diseases. Berberine (BBR), an important isoquinoline alkaloid found in various medicinal plants, has been shown to have multiple pharmacological effects and therapeutic applications. In view of its low bioavailability, increasing evidence indicates that the gut microbiota may serve as a target for the multifunctional effects of BBR. Under the pathological conditions of AS and metabolic diseases, BBR improves intestinal barrier function and reduces inflammation induced by gut microbiota-derived lipopolysaccharide (LPS). Moreover, BBR reverses or induces structural and compositional alterations in the gut microbiota and regulates gut microbe-dependent metabolites as well as related downstream pathways; this improves glucose and lipid metabolism and energy homeostasis. These findings at least partly explain the effect of BBR on AS and metabolic diseases. In this review, we elaborate on the research progress of BBR and its mechanisms of action in the treatment of AS and metabolic diseases from the perspective of gut microbiota, to reveal the potential contribution of gut microbiota to the multifunctional biological effects of BBR.